Reconciling Globalization and Localization in developing the Architectural Heritage of the United Arab Emirates (UAE) - Atry, Seyyedeh Dena Barzanjeh; Khan, Tareef Hayat; Tajuddin Mohamad Rasdi, Mohamad (Advances in Social Sciences Research Journal, 2017)
This study investigated the impact of Globalization and Localization on architectural design evident in the unprecedented building boom in the United Arab Emirates (UAE), and the relationship between such impact and its influence on the Architecture of these new developments. To date, although research on the stunning architecture in UAE has focused on several aspects, much of the attention has been paid to the descriptions of the mega projects in the contexts of its historical development, documentation of the new developments, and discourse on the role and function of these new developments in relation to social aspects. In contrast, this study aimed to determine: the impact of the coexistence of these forces of change on the built environment in UAE in order to understand the impact of Globalization and Localization, and the rise of Traditionalism and Modernism during this transformation process. This research adopted a multi-disciplinary logic of inquiry combining the interpretivist and structuralist paradigms in association with a framework incorporating both semiotics and hermeneutics, in order to interpret the Star Architects’ intentions and associated actions during the creation of these structures. Research data were collected from archival records, books and various electronic sources. Data analysis revealed that there is a dialectic relationship between Globalization and the design of these stunning developments in UAE. This paper therefore, can offer new insights, which is likely to add to knowledge in this field by widening and strengthening the understanding of Globalization, Localization and architectural historical theory in UAE.